Biochemical characterization of fruits of Lycium spp. in Ukraine - M. Zhurba; O. Vergun; S. Klymenko; I. Szot (Regulatory Mechanisms in Biosystems, 2021)
Fruits of Lycium possess therapeutic properties due to which they are used in traditional and folk medicine and can be used as a kind of functional food. The objective of this study was to evaluate the biochemical characterization of Lycium L. (L. barbarum L., L. chinense Mill. and L. truncatum Y. C. Wang) fruits for 16 cultivars and varieties from the collections in the M. M. Gryshko National Botanical Garden of NAS of Ukraine (Kyiv). This study was aimed at determining the concentration of nutrients in the Lycium fruits. Individual genotypes of three Lycium species: L. barbarum, L.chinense, and L. truncatum, differed in such features as the content of dry matter, sugars, vitamin C, β-carotene, acidity, and tannins in the fruit. Fruits of Lycium spp. are a valuable source of nutrients such as vitamin C (4.38–121.0 mg 100g–1 FW), β-carotene content (1.45–5.52%), and tannin (0.12–1.34%). The sugar content (13.83–20.87%) and acidity of the fruit (0.23–4.62%) meet the consumers' requirements for fresh fruit. The cultivar Amber Sweet (L. chinense) had fruits of which the similarities between biochemical characteristics of different studies genotypes were the lowest. The cv. Amber Sweet was characterized by fruit with high sugar content, very high vitamin C content, average acid content, low tannins and β-carotene content, and the lowest dry matter content. Furthermore, a distinctive feature of the other tested genotypes was the yellow colour of the fruit. The data obtained can be used for further selective work.